Ancient greek philosophy - "Tankha, Vijay" (New Delhi, 2006)
Western thought is firmly grounded in the works of the predecessors of Aristotle and Plato?often collectively called the pre-Socratics. Seminal thinkers like Anaximander, Heraclitus, Pythagoras, Parmenides and many others defined, two centuries before Plato and Aristotle, the nature and ambit of the nascent discipline of philosophy. In order to appreciate the subsequent developments in the field, it is necessary to understand the diversity of philosophical issues dealt with and the variety of philosophical methods employed in the works of these pre-Socratics. In this book the principal fragments of these early thinkers are translated and discussed at length . The author contends that pre-Socratic philosophy is not to be looked at as a matter of mere historical interest . Although these works survive only in fragments, they have been the subject of study and reflection by the whole of the western philosophical tradition. The range of these pioneers is truly remarkable: from the first cosmological speculations of the Milesians, through the discovery and development of a complex notion of the self, and the possibility of knowing?and being able to state?what is true, these thinkers raised fundamental questions about the nature of the world and man's place in it. In them one can see the birth of both metaphysics and epistemology, as well as the first definitive steps in logic and ethics . Using the perspectives of their closest contemporaries, the author looks closely at the problems and issues raised by the pre-Socratics, providing at once an in-depth introduction to the whole of classical Greek philosophy. As this lucid and detailed discussion on the pre-Socratics leads one to the very origins of the discipline of philosophy, this book would prove to be of abiding interest to all students and teachers of philosophy and the history of ideas.
Keywords: "Philosophy,Ancient-Greek"